PEMBAGIAN HARTA WARIS PADA SURAH AN NISA DALAM TEORI INTERPRETASI FUNGSI JORGE. JE. .GRACIA - Harahap, Nurhanipah (STIQ Miftahul Huda Rawalo, 2024)
The existence of hermeneutics that emerged into the world of interpretation of the qur’an has given many different influences to muslim scholars around the world. Hermeneutics is considered to be able to reveal the meaning of the other side of the previous interpretation. Initially, the use of hermeneutics was only used to understand the bible. Previously, hermeneuticz in understanding the qur’an was consideres something that could not to be tolerated because of its existence. This article contains the interpretation of thr qur’an surah an Nisa 11 and 12 contains the distribution of inheritance for sons and daughters in Islam. Substantially contained five things discussed in the verse, namely, rationalization related to differences in the inheritance of men and women, the inheritance of children, the inheritance of parents, the time of division, and the lesson. This study uses qualitative research using Jorge J.E’s hermeneutic approach. Gracia in her book entitled A Theory Of Textuality.